Integrating the Western Balkans into the EU
XXIV, 452 p. 26 illus., 25 illus. in color.
Keywords: Only Milica Uvalic could gather such a stellar group of authors on relations between countries in Southeastern Europe and the European Union; their wide range of perspectives is both timely and extremely valuable for scholars and policy makers alike. ---Susan L. Woodward, The Graduate Center, City University of New York, USA This book is crucial reading for anyone who wants to understand why it is taking so long to integrate the Western Balkans countries into the European Union. It addresses the misconceptions on both sides by scholars from a variety of disciplines, providing real understanding and insight. ---Saul Estrin, London School of Economics, UK Among the main stumbling blocks of European Union-Western Balkan integration are the differences in perceptions on both sides. Today, the gap between what the Western Balkan politicians and citizens think about the European Union and what the politicians and citizens in the EU member states think about the Western Balkans is probably wider than ever. This volume offers fresh insights about these misperceptions and how to possibly bridge the gap. It examines perceptions about the region’s “European perspectives” both on the side of the six Western Balkan countries - Albania, Bosnia and Herzegovina, Kosovo, Montenegro, North Macedonia and Serbia – and the key European Union member states (Italy, Germany, Croatia), international donors, USA. An analysis of the diverse views regarding the prospects of EU – Western Balkan integration is today highly relevant, in view of the current uncertainties regarding European Union’s enlargement policy, particularly after the attack of Russia on Ukraine and candidate status granted to Ukraine and Moldova. Milica Uvalic is Professor at the University of Perugia, Italy. She was also member of the UN Committee for Development Policy and Assistant Minister in the first post-Milošević government in FRYugoslavia. Recent publications include Towards Economic Inclusion in the Western Balkans coedited with W. Bartlett (Palgrave, 2022) and The Economic and Investment Plan for the Western Balkans co-authored with W. Bartlett and M. Bonomi (European Parliament, 2022).